Uji Aktivitas Analgesik Tablet Asam 4-(Klorometil)Salisilat pada Mencit Putih dengan Metode Writhing Test dan Hotplate - Tiffany, Angela; Ribka Abiati, Meidelin; Foe, Kuncoro; Tjahjono, Yudy; Caroline; Esar, Senny Yesery; Hadinugroho, Wuryanto (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
Acetylsalicylic acid is an analgesic drug that still popularly used. However, acetylsalicylic acid may result undesirable side effect of gastrointestinal as it can cause gastric ulcer to bleeding. Previous research has succeeded synthesizing new compound derived from salicylic acid, namely 4-(chloromethyl)salicylic acid which has the potential to reduce its side effects with a better pharmacological effects than acetylsalicylic acid. In its development, the formulation of the compound in tablet dosage form has been carried out. However, until now there has not been a pharmacological test to determine whether it still provides a greater effect than acetylsalicylic acid after being formulated. This study is to test the analgesic activity of 4-(chloromethyl)salicylic acid tablets in albino mice using writhing test and hotplate methods. Analgesic activity test using the hotplate method was carried out on albino mice which given the suspension of the tablet sample and the observations were made in a periodic of time. Analgesic activity test using writhing test method was carried out in 0.6% acetic acid-induced albino mice, where the suspension of the tablet was administered 30 minutes before administration of acetic acid. Analgesic activity was assessed by counting the number of writhings, and the results were statistically compared with one-way ANOVA. Tests were also performed on acetylsalicylic acid as a positive control and suspension as a negative control group. There were significant differences (P<0.05) of the analgesic activity observed among groups. Both methods show that 4-(chloromethyl)salicylic acid tablets provide stronger analgesic activity than acetylsalicylic acid.